Microstructural Characters of Lyctinae and Dinoderinae (Coleoptera: Bostrichidae) - Lan-Yu Liu (Psyche: A Journal of Entomology)
Thirty-three species belonging to the bostrichid subfamilies Lyctinae and Dinoderinae were examined by low vacuum ESEM without sputtering. Eight types of microsculpture, five types of hair insertion, and 14 types of hair were found on the elytral disc and declivity. The different types of microstructure are described and illustrated with ESEM photos of each type. Surface microstructures provide additional taxonomically useful characters which can help to distinguish easily confused species. The study also showed that specimens can be examined under ESEM without any damage.